2000
DOI: 10.4049/jimmunol.165.6.3451
|View full text |Cite
|
Sign up to set email alerts
|

Mice with Spontaneous Pancreatic Cancer Naturally Develop MUC-1-Specific CTLs That Eradicate Tumors When Adoptively Transferred

Abstract: Pancreatic cancer is a highly aggressive, treatment refractory cancer and is the fourth leading cause of death in the United States. In humans, 90% of pancreatic adenocarcinomas overexpress altered forms of a tumor-specific Ag, mucin 1 (MUC1; an epithelial mucin glycoprotein), which is a potential target for immunotherapy. We have established a clinically relevant animal model for pancreatic cancer by developing a double transgenic mouse model (called MET) that expresses human MUC1 as self molecule and develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 52 publications
2
52
1
Order By: Relevance
“…To evaluate MUC1 expression, tumors and normal tissues were fixed in methacarn (60% methanol, 30% chloroform, 10% glacial acetic acid), paraffin embedded, and sectioned for immunohistochemical analysis as previously described [16,17]. In a separate experiment, following enumeration of the adenomas, the intestinal segments were formalin fixed and individual tumors were excised from each segment and placed in cassettes with sponges to maintain orientation.…”
Section: Immunohistochemistry and Histologymentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate MUC1 expression, tumors and normal tissues were fixed in methacarn (60% methanol, 30% chloroform, 10% glacial acetic acid), paraffin embedded, and sectioned for immunohistochemical analysis as previously described [16,17]. In a separate experiment, following enumeration of the adenomas, the intestinal segments were formalin fixed and individual tumors were excised from each segment and placed in cassettes with sponges to maintain orientation.…”
Section: Immunohistochemistry and Histologymentioning
confidence: 99%
“…Splenocytes were isolated from vaccinated mice and incubated in 6 well plates at a density of 1×10 6 cells/mL with the MUC1 TR peptides and the hepatitis B virus core antigen pan helper peptide, each at 20 ng/mL for 48 h as previously described [16]. The supernatants were harvested and analyzed for the presence of IFN-γ by ELISA (Pierce Endogen, Rockford IL).…”
Section: Cytokine Production Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…MUC1 (CD227) is a membrane-tethered mucin glycoprotein expressed on the apical surfaces of normal glandular epithelia and it is over expressed and aberrantly glycosylated in >70% of human colon cancer [1][2][3]. Recent description of MUC1 as a target for cytotoxic T lymphocytes (CTLs) has raised interest in using this protein as a target for immunotherapy [4][5][6][7][8][9][10][11][12][13][14]. Several preclinical and clinical trials targeting the tumor-associated MUC1 antigen have elicited strong anti-tumor CTLs [1,2,12,[14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not known if the use of dendritic cells or mixed APCs for the active immunotherapy of cancer has an advantage over more conventional vaccine approaches, which are simpler and much less expensive. We usually propose WT1, MUC1, CEA, CA125, HER-2/neu, and PSA as cancer antigens for DC based therapy according to the patient's primary lesion and elevated tumor marker (Sugiyama, 2005;Mukherjee et al, 2000;Nair et al, 1999;Larbcurrentet et al, 2007). It has been reported that WT1 and MUC1 is antigens with high immunogenicity and their-targeted immunotherapy have confirmed its safety and clinical efficacy, although there is few description concerning cancer vaccine adapting WT1 and MUC1 simultaneously to cancer antigen (Ramanathan et al, 2005).…”
mentioning
confidence: 99%